2015
DOI: 10.1186/s13104-015-1041-z
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in school-aged adolescents: design of a social network survey in six European countries

Abstract: BackgroundIn Western countries, smoking accounts for a large share of socio-economic inequalities in health. As smoking initiation occurs around the age of 13, it is likely that school context and social networks at school play a role in the origin of such inequalities. So far, there has been little generic explanation of how social ties at school contribute to socio-economic inequalities in smoking. The SILNE (Smoking Inequalities – Learning from Natural Experiments) survey was designed to test the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 63 publications
1
47
0
8
Order By: Relevance
“…The questionnaire included questions on several dimensions of socio‐economic status, life‐style and wellbeing at school. For more information on this survey, including design, sample size and ethical approval, see Lorant et al 13.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire included questions on several dimensions of socio‐economic status, life‐style and wellbeing at school. For more information on this survey, including design, sample size and ethical approval, see Lorant et al 13.…”
Section: Methodsmentioning
confidence: 99%
“…As explained elsewhere, adolescents (ego) were asked to nominate up to five best friends (alters): "Who are your best and closest friends?" (Lorant et al, 2015). They were told that they could nominate friends enrolled in two grades of their schools corresponding to the 14-16 age group, using a directory that contained the names of all adolescents in those grades.…”
Section: Methodsmentioning
confidence: 99%
“…We used data from the SILNE study: a whole-network study whose detailed design, including ethical review, has been presented elsewhere (Lorant et al, 2015). The survey was administered between January and November of 2013 to adolescents in 50 schools in six European cities of similar population size and income and with employment rates close to the national average.…”
Section: Datamentioning
confidence: 99%
“…Inequalities: Learning from Natural Experiments (SILNE) survey. 27 In this study, we combined these data sources to extrapolate the nicotine dependence rates found in SILNE (i.e. six EU countries) to the EU as a whole, using the smoking prevalence data from HBSC.…”
Section: And the 2013 Smokingmentioning
confidence: 99%